Screening South American potato landraces and potato wild relatives for novel sources of late blight resistance - Pérez, W.; Alarcón, L.; Rojas, P.; Correa, Y.; Juarez, H.; Andrade-Piedra, J.L.; Anglin, Noelle L.; Ellis, David (Scientific Societies, 2022)
Late blight (LB) caused by the oomycete Phytophthora infestans is one of the most important biotic constraints for potato production worldwide. This study assessed 508 accessions (79 wild potato species and 429 landraces from a cultivated core collection) held at the International Potato Center (CIP) genebank for resistance to LB. One P. infestans isolate belonging to the EC-1 lineage, which is currently the predominant type of P. infestans in Peru, Ecuador, and Colombia, was used in whole plant assays under greenhouse conditions. Novel sources of resistance to LB were found in accessions of Solanum albornozii, S. andreanum, S. lesteri, S. longiconicum, S. morelliforme, S. stenophyllidium, S. mochiquense, S. cajamarquense, and S. huancabambense. All of these species are endemic to South America, and thus, could provide novel sources of resistance to potato breeding programs. We found that the level of resistance to LB in wild species and potato landraces cannot be predicted using altitude and bioclimatic variables of the locations where the accessions were collected. The high percentage (73%) of susceptible potato landraces to LB in our study suggests the importance of implementing disease control measurements, including planting susceptible genotypes in less-humid areas/seasons, or switching to genotypes identified as resistant. In addition, this study points out a high risk of genetic erosion in potato biodiversity in high altitudes of the Andes due to susceptibility to LB in the native landraces, which has been exacerbated by climatic change that favors the development of LB in those regions.